THE INTESTINAL INSUFFICIENCY SYNDROME AND THE SYSTEMIC INFLAMMATORY RESPONSE SYNDROME IN ACUTE PERITONITIS IN CHILDREN - Cristina Șerban; Georgiana Bianca Constantin; Daniela Mihalache; Alina Calin; Norin Forna; Mădălin Guliciuc (Romanian Journal of Oral Rehabilitation)
Background:According to many published research in the literature, acute peritonitis in children is a topic of interest, first due to the disorders produced by the growing organism and, on the other hand, due to the problems that may appear during the surgical intervention, becoming the main source of intraoperative and postoperative accidents. Materials and methods:We made a retrospective analysis on 127 patients, hospitalized and treated in two clinics from Galați, between 2018 and 2023, with the diagnosis of acute peritonitis. The inclusion criteria were the age between 0 months and 18 years, the presence of signs of peritonitis and endotoxicosis. We performed a statistical analysis using the XLSTAT 2017 program, with descriptive analytical methods, univariate and multivariate statistical analytical methods. Results:We analyzed the risk factors that allowed us to propose a prognostic score in assessing the severity of acute peritonitis in children. Conclusions:The high frequency of complications, the increased interest in this pathology from the perspective of abdominal sepsis, raises the issue of acute peritonitis in children as a public health problem. The aim of this study was to do a research of the intestinal insufficiency syndrome in the evolutionary stages of acute peritonitis in children, in order to obtain a prognostic score in assesing the severity of acute peritonitis in children.